2018
DOI: 10.4142/jvs.2018.19.6.788
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of ribavirin and vaccine for protection during early infection stage of foot-and-mouth disease

Abstract: In many countries, vaccines are used for the prevention of foot-and-mouth disease (FMD). However, because there is no protection against FMD immediately after vaccination, research and development on antiviral agents is being conducted to induce protection until immunological competence is produced. This study tested whether well-known chemicals used as RNA virus treatment agents had inhibitory effects on FMD viruses (FMDVs) and demonstrated that ribavirin showed antiviral effects against FMDV in vitro/in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Similar to 5-FU, it is mutagenic for many RNA viruses [62,[70][71][72][73][74][75]. Ribavirin has been in clinics for many years to treat HCV (in combination with pegylated interferon) [76], FMDV [77] and poliovirus [78]. Additionally, ribavirin in combination with interferon-α2a or α2b has been shown to inhibit MERS-CoV infection [79][80][81].…”
Section: -Fluorouracil (5-fu)mentioning
confidence: 99%
“…Similar to 5-FU, it is mutagenic for many RNA viruses [62,[70][71][72][73][74][75]. Ribavirin has been in clinics for many years to treat HCV (in combination with pegylated interferon) [76], FMDV [77] and poliovirus [78]. Additionally, ribavirin in combination with interferon-α2a or α2b has been shown to inhibit MERS-CoV infection [79][80][81].…”
Section: -Fluorouracil (5-fu)mentioning
confidence: 99%
“…We think that a complementary approach using antiviral molecules would be ideal to complement vaccination, reduce viral spreading in equine structures and contain EAV outbreaks. This is supported by a recent study showing that a global strategy based on vaccination combined with drug therapies enhances protection against foot-and-mouth disease 10 . In our study, we have developed a high-throughput cell-viability assay based on infected equine dermal cells.…”
mentioning
confidence: 62%
“…Ribavirin is a synthetic nucleoside analogue that structurally resembles guanosine [45], and can interfere with the synthesis of viral mRNA. It has been demonstrated that ribavirin is a common anti-picornavirus drug with low cytotoxicity [46][47][48][49][50]. Its antiviral effect was generally described in terms of the SI value.…”
Section: Discussionmentioning
confidence: 99%